2020
DOI: 10.31083/jomh.v16i4.312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Hypobaric Hypoxia on Metabolic Response, Skeletal Muscle Oxygenation, and Exercise Performance in Healthy Males

Abstract: ObjectiveThis study aimed to evaluate the effect of various levels of hypoxia versus normoxia on exercise performance, measured by metabolic parameters and skeletal muscle oxygenation profiles during graded exercise test (GXT) in healthy men. MethodsIn this randomized crossover trial, 11 healthy male participants (age 21.5 ± 2.3 years) performed the GXT using a cycle ergometer at sea-level (760 torr) and at various hypobaric hypoxia: 633, 526, and 433 torr, corresponding to simulated altitudes of 1500, 3000, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…The unchanged mean VCO 2 , between CONLD and CONLD-BH, suggests that the H + buffering, associated with the lactate production of anaerobic glycolysis, has been reflected in the observed increase in P ET CO 2 and that the BH did not impose a greater anaerobic glycolytic contribution. The unchanged post-exercise [La – ] between CONLD and CONLD-BH trials is in contrast to other studies that have reported increased [La – ] accumulation during incremental ( Seo et al, 2020 ) (50 W + 12.5 W/min to exhaustion) and intermittent ( Lim et al, 2018 ) exercise under hypoxic or apneic condition, respectively. However, these studies were performed at much higher supra-LT PO, which would elicit much greater blood [La – ].…”
Section: Discussioncontrasting
confidence: 99%
“…The unchanged mean VCO 2 , between CONLD and CONLD-BH, suggests that the H + buffering, associated with the lactate production of anaerobic glycolysis, has been reflected in the observed increase in P ET CO 2 and that the BH did not impose a greater anaerobic glycolytic contribution. The unchanged post-exercise [La – ] between CONLD and CONLD-BH trials is in contrast to other studies that have reported increased [La – ] accumulation during incremental ( Seo et al, 2020 ) (50 W + 12.5 W/min to exhaustion) and intermittent ( Lim et al, 2018 ) exercise under hypoxic or apneic condition, respectively. However, these studies were performed at much higher supra-LT PO, which would elicit much greater blood [La – ].…”
Section: Discussioncontrasting
confidence: 99%